Vestibular function tests are helpful in differentiating between Menière’s disease and vestibular migraine - Vosbeek, Eleonora G. M.; Seelen, Meinie; Vingerhoed, Aliede M.; Schermer, Tjard R.; Cannegieter, Suzanne C.; Terwindt, Gisela M.; Bruintjes, Tjasse D. (Frontiers in Neurology, 2025)
AimMenière’s disease (MD) presents with episodic vertigo and auditory symptoms. Vestibular migraine (VM) typically contains migraine features associated with the vertigo attacks. Distinguishing MD from VM can be challenging due to overlap in symptomatology. To assist in the differentiation between the two, this study aimed to compare auditory and vestibular symptoms and functions in MD and VM, and to assess the diagnostic value of the video head impulse test (vHIT) and caloric test.MethodsA cohort study was performed at a tertiary dizziness clinic in the Netherlands in MD and VM patients seen in our clinic from January 2018 until September 2024. Patients were diagnosed based on the Bárány Society criteria. We collected demographic characteristics, symptoms at presentation, results of pure-tone audiometry (PTA), caloric testing, and vHIT. Positive predictive value (PPV) and negative predictive value (NPV) of the vHIT and caloric test were calculated and the optimal unilateral weakness cut-off value was determined.ResultsThe mean age of the MD patients (n = 194) was 60.2 ± 13.4 years, with 46.4% females. The VM patients (n = 101) had a mean age of 50.2 ± 14.6 years, with 86.1% females. Not only MD patients, but also 65.7% of VM patients experienced at least one aural symptom during vertigo attacks. An abnormal caloric test, abnormal horizontal vHIT, and catch-up saccades during the vHIT were observed more frequently in MD than in VM patients. The vHIT had a PPV of 81% and an NPV of 36% to distinguish MD from VM. Additionally, in patients with a normal vHIT, the caloric test had a PPV of 82% with an NPV of 55%. Increasing the unilateral caloric weakness threshold to 34%, increased the PPV to 90%, with an NPV of 52%.ConclusionWhile the diagnosis of MD and VM is based on history and audiometry findings, vHIT and caloric testing may aid in differentiating between the two diseases in ambiguous cases. If either the vHIT or caloric test is abnormal, a diagnosis of MD is more likely. The optimal PPV and NPV to differentiate between MD and VM was found with a unilateral caloric weakness threshold of 34%.